Effect of Physical Development Self-Assessment Indicators on Value Orientation Structure Formation in Senior School Age Students - Bakiko, Ihor; Krutsevich, Tetiana; Trachuk, Sergii (Physical Education Theory and Methodology, 2022)
Background. Physical education as a subject in general secondary education institutions aims not only to solve health and educational problems but also to form a value attitude to health, healthy lifestyle, fostering the interest in and the need for physical activity. Research purpose. The study aims to investigate the relationship between senior school age students’ value orientations and physical development self-assessment indicators to determine incentives to increase motivation for self-improvement by means of physical education. Materials and methods. The research methods used to solve the tasks set in the paper were as follows: analysis and generalization of data of scientific and methodological literature; content analysis; comparison and juxtaposition method; Ye. Bochenkova’s test-questionnaire Self-description of physical development, M. Rokych’s technique for defining value orientations; methods of mathematical statistics. Results. Based on examining correlations between the 11th grade students’ terminal values and physical development self-assessment, a tendency was found to shift the priority of youth values towards life values, values of professional realization, and values of interpersonal relationships. Based on the results of the study, we found that the formation of value orientations in boys and girls in high school can affect self-esteem, which in turn is a stimulus for self-improvement and, through an effective component of physical activity, increases the importance of “health” for senior school age boys. On the other hand, girls have no such pattern, and the value of “health” is declarative for them. Conclusions. It has been determined that the formation of value orientations through an effective component of physical activity can affect the self-esteem of boys and girls, which in turn is an indicator of self-awareness and expresses the individual’s attitude to himself and is the basis for regulating their own behavior.